A visual approach to support Change Impact Analysis in object-oriented source code - Biazini, Renan Pereira [UNESP] (2020)
Change Impact Analysis aims to identify parts of a system affected by the proposed change implementation. Although one may find in literature techniques to automate the impact identification process, it is still highly dependent on the experience with the analyzed software. Studies in this area do not focus on the analysis of the possible impact identified by the techniques. In this paper, we propose a visual approach to deal with the results generated by applying an impact analysis technique to oriented source code. Coordinating visual mappings makes it possible to identify impacted entities regarding the individual difficulty of maintenance. Also, it is possible to determine how are affected the entities. In this paper, we present the implemented approach (tool VisImpala), the generated views, how to interpret them, and the lessons learned.